Integrated Eco-Health approach significantly reduces helminth infections in endemic Khong islands with emphasis on Schistosoma mekongi - Somphou Sayasone; Youthanavanh Vonghachack; Shang Xia; Shan Lv; Xiao-Nong Zhou; Peter Odermatt (Infectious Diseases of Poverty, 2024)
Abstract Background Helminth infections, including Opisthorchis viverrini, hookworm, and Trichuris trichiura, are prevalent in Khong district, Champasack province, southern Lao People’s Democratic Republic (PDR). Schistosomiasis caused by Schistosoma mekongi is of public health concern on the islands of the Khong district. This study aimed to assess the impact of an Eco-Health/One-Health approach in combination with mass drug administration (MDA) to reduce these helminth infections. Methods We conducted a community intervention using a stepped-wedge trial approach on two endemic islands (Donsom and Donkhone) of the Khong district, Champasack province, Lao PDR, between April 2012 and March 2013. In each study village, 30–40 households were randomly selected. All members of selected households, who were at home during the study period were invited to participate in the study. A baseline study was conducted to assess helminth infections, knowledge attitudes and practices toward Schistosoma mekongi infection, behavior of open defecation and availability of latrine at home. After the baseline (T0), the Eco-Health/One-Health approach was implemented on Donsom (intervention) and Donkhone island (control). An assessment was conducted in 2014 (T1), one year after the completion of intervention implementation, to assess the short-term impact of the Eco-Health/One-Health approach on helminth infections and compare intervention and control islands. Later in 2015, the Eco-Health/One-Health approach was implemented on control island (Donkhone). After the implementation of intervention, the parasitological assessments were conducted annually in humans in 2015 (T2), in 2016 (T3) and in 2017 (T4), and in dogs in 2017 (T4) to evaluate the long-term impact of the intervention on helminth infections. Frequency was used to describe the prevalence of helminth infections. Logistic regression was applied to associate the KAP (knowledge, attitudes, and practices and open defecation behavior) and the reduction of helminth infections between intervention and control islands. The reduction in prevalence pre- and post-intervention was associated using a McNemar test. A two-independent sample t-test was applied to compare the mean eggs per gram (EPG) of helminth infections between control and intervention islands. A paired t-test test was used to compare the mean EPG of stool samples before (baseline) and after (follow-up) interventions for the two islands separately. A P-value lower than 0.05 was considered statistically significant. Results Eco-Health/One-Health approach appears to be associated with reduction in prevalence of S. mekongi by 9.0% [odds ratio (OR) = 0.49, P = 0.003] compared to the use of mass drug administration alone (control island). Additionally, this intervention package significantly reduced O. viverrini infection by 20.3% (OR = 1.92, P < 0.001) and hookworm by 17.9% (OR = 0.71, P = 0.045), respectively. Annual parasitological assessments between 2012 and 2017 showed that the Eco-Health/One-Health approach, coupled with MDA, steadily reduced the prevalence of S. mekongi on the intervention island from 29.1% to 1.8% and on the control island from 28.4% to 3.1%, respectively. Conclusions The study findings suggest that the Eco-Health/One-Health approach appears to be associated with a significant reduction in prevalence of S. mekongi and helminth co-infections, particularly hookworm and T. trichiura. Therefore, implementing the Eco-Health/One-Health approach in schistosomiasis-endemic areas could accelerate the achievement of national goals for transmission interruption by 2025 and elimination by 2030.